Prevalence of musculoskeletal disorders among administrative staff at the healthcare office during COVID-19 pandemic - Fatin Nurdiana, Mohd Radzi; Nor Aslina, Abd Jalil; Mohammad Adam, Adman (UTeM, 2022)
Administrative staff in the healthcare office exposed to a higher risk of developing musculoskeletal disorders (MSDs) with the increasing daily office workload, especially during the COVID-19 pandemic. This paper aims to determine the prevalence of MSDs among administrative staff in a healthcare office in Selangor. A total of 103 respondents participated in this study. The result shows the prevalence of MSDs was present in all body regions among administrative staff at the healthcare office, with the highest percentage in the lower back region. The majority of male administrative staff had lower back pain or discomfort (n=13, 61.9%). However, the majority of female administrative staff had neck pain or discomfort (n=56, 68.3%). In conclusion, the prevalence of MSDs among administrative staff in the healthcare office was most common in the lower back region. Therefore, preventive and mitigation of MSDs among administrative staff at the healthcare office are essential during the COVID-19 pandemic, such as improving ergonomics in the office.